Informal Entrepreneurship in Developing Economies: The Impacts of Starting up Unregistered on firm Performance - Williams, Colin C.; Martinez–Perez, Alvaro; Kedir, Abbi M. (Entrepreneurship Theory and Practice, 2017)
To advance understanding of the entrepreneurship process in developing economies, this article evaluates whether registered enterprises that initially avoid the cost of registration, and focus their resources on overcoming other liabilities of newness, lay a stronger foundation for subsequent growth. Analyzing World Bank Enterprise Survey data across 127 countries, and controlling for other firm performance determinants, registered enterprises that started up unregistered and spent longer operating unregistered are revealed to have significantly higher subsequent annual sales, employment, and productivity growth rates compared with those that registered from the outset. The theoretical and policy implications are then discussed.